Narrative problem based learning in Biomedical Science - Md. Akim, Abdah (Universiti Putra Malaysia Press, 2020)
Problem-based learning (PBL) is a process of acquiring knowledge based on the problem given. This method will give understanding on the underlying problem. PBL improves teaching practices by replacing traditional teaching methods. It reduces the passive information giving process thus making undergraduate education a platform for life¬long learning. PBL reverses the traditional approach to teaching and learning. Problem based learning is a method of teaching and learning where the students need to be proactive in their discussion. Case studies were given and students were required to explore from all aspect of Biomedical Science to help them to understand the situation underlying it. Narrative Problem-based Learning was based on non_ction events. It was taken from the experience of those who underwent the events. Triggers presented in each topic were aimed to help final year Biomedical students to integrate knowledge gained throughout their study in the field of Biomedical Sciences.